2011
DOI: 10.1111/j.1469-0691.2011.03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of multidrug-resistant organisms in patients with healthcare-associated pneumonia requiring hospitalization

Abstract: Healthcare-associated pneumonia (HCAP) includes a broad spectrum of patients who acquire pneumonia through outpatient contact with the health system. Although limited prospective data exist, it has been suggested that all patients with HCAP should receive empirical therapy with a multidrug regimen directed against drug-resistant organisms. We aimed to determine the differences in aetiology and outcomes between HCAP groups and a community-acquired pneumonia (CAP) group, and to assess the presence of antibiotic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
2
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 19 publications
(28 reference statements)
6
81
2
4
Order By: Relevance
“…6 The validity of these antimicrobial guidelines for the treatment of nursing home patients has been most challenging because the microbiology of NHAP varies widely among published reports, according to study design, severity of illness, and colonization with resistant organisms due to prior hospitalization. 15 Our results confirm the previously published etiologic difference between NHAP from the United States and Europe. 7 In particular, Staphylococcus species were identified as the prominent pathogen in the United States (52%) as opposed to S. pneumoniae in Europe (46%) and Latin America (25%).…”
Section: Etiologysupporting
confidence: 83%
“…6 The validity of these antimicrobial guidelines for the treatment of nursing home patients has been most challenging because the microbiology of NHAP varies widely among published reports, according to study design, severity of illness, and colonization with resistant organisms due to prior hospitalization. 15 Our results confirm the previously published etiologic difference between NHAP from the United States and Europe. 7 In particular, Staphylococcus species were identified as the prominent pathogen in the United States (52%) as opposed to S. pneumoniae in Europe (46%) and Latin America (25%).…”
Section: Etiologysupporting
confidence: 83%
“…pneumoniae was the most frequent pathogen of HCAP, and the frequency of atypical pathogens was 9.0 , results compatible with those of previous reports 3,4,[9][10][11][12] . Although the frequency of atypical pathogens was lower in HCAP than in CAP, the 9.0 incidence of atypical pathogens should not be ignored.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, urinary antigen tests, serological analysis, and RIDT were also used in the etiological diagnosis, with cases of unknown etiology also included. More recent studies have revealed that the most frequent pathogen is S. pneumoniae, and atypical pathogens have been detected in 0.7 to 16.1 of cases 3,4,[9][10][11][12] . In the present study, S.…”
Section: Discussionmentioning
confidence: 99%
“…Studies attempting to validate the Table 1 have demonstrated limited accuracy in the precision of these models when applied to an independent population, indicating again that local ecology and case mix drive the rates of MDR infection in differing regions and countries [5,13,14]. Similarly, specific HCAP risk factors and the presence of multiple HCAP risk factors have been linked to increased risk of pneumonia attributed to S.aureus and P. aeruginosa, respectively [15]. However, the clinical utility of these specific risk factor profiles for improving the prescription of antibiotics to patients with pneumonia has not been demonstrated.…”
mentioning
confidence: 99%